Exploring the peaks and valleys in the number of births in Portugal - Caleiro, António (2012)
In spite of the remarkable downward trend in fertility that characterizes Portugal, birth seasonality is still evident. A time series analysis of the data shows that, in general, May and September are months where more births take place and that December and February are the months with the lowest figures. In particular, the September peak in births, which is the most remarkable result, is shown to be related to end-of-year (economic) expectations.